A short expedient synthesis of [14C]Ticlopidine. (27th January 2014) - Hickey, Michael J.; Kingston, Lee P.; Allen, Paul H.; Johnson, Tim; Wilkinson, David J.
<x xml:space="preserve">Abstract</x> To support the development of a reactive metabolite strategy, the preparation of several radiolabelled compounds such as [14C] Ticlopidine was required. In this report, we describe a facile and rapid synthesis of [14C] Ticlopidine starting from [14C] carbon dioxide. The compound was radiolabelled in the 2‐chloromethyl portion of the molecule with a specific activity of 53.4 mCi/mmol and with a radiochemical purity of 98.5%. Storage stability was best as the hydrochloride salt in an ethanol solution. Copyright © 2014 John Wiley & Sons, Ltd.